2006
DOI: 10.1021/la061152w
|View full text |Cite
|
Sign up to set email alerts
|

New Anisotropic Ceramic Membranes from Chemically Fixed Dissipative Structures

Abstract: The formation of highly ordered capillaries in alginate gels is due to a dissipative convective process resulting from opposing diffusion gradients and friction. Ceramic membranes with an anisotropic pore structure have been gained from this self-organization process by incorporating inorganic particles into the gel matrix, followed by subsequent ion exchange, drying, and sintering. The aim of this study was to overcome existing preparative deficiencies and to optimize the capillary structure and surface prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
0
15
0
4
Order By: Relevance
“…3(b)-(e). It is known to us that the cation-induced gelification of alginate is limited by the unidirectional diffusion of Me 2+ metal ions through alginate sol, so the generation of capillary structures is a convective process resulting from two opposing diffusion gradients and friction between the contracting alginate chains and surrounding solution [20]. Therefore, the increasing viscosity of slurries with solid loading would definitely retard the mobility of the two exchanging counter ions ([Alg − ] and [Ca 2+ ]) during the dissipative process, and hinder the even diffusion of Ca 2+ into the slurry and the uniform cross-link of Ca 2+ with NaAlg, which resulted in the increase of pore size and deformation of pore shape.…”
Section: Porosity and Microstructuresmentioning
confidence: 99%
“…3(b)-(e). It is known to us that the cation-induced gelification of alginate is limited by the unidirectional diffusion of Me 2+ metal ions through alginate sol, so the generation of capillary structures is a convective process resulting from two opposing diffusion gradients and friction between the contracting alginate chains and surrounding solution [20]. Therefore, the increasing viscosity of slurries with solid loading would definitely retard the mobility of the two exchanging counter ions ([Alg − ] and [Ca 2+ ]) during the dissipative process, and hinder the even diffusion of Ca 2+ into the slurry and the uniform cross-link of Ca 2+ with NaAlg, which resulted in the increase of pore size and deformation of pore shape.…”
Section: Porosity and Microstructuresmentioning
confidence: 99%
“…The following equation shows the gelation reaction: 2NaAlg+CaCl2Ca(Alg)2+2NaCl The alginate chains are cross‐linked by the calcium ions. The unidirectional diffusion of the calcium ions through the sol causes orientation and densification of the alginate chains forms capillaries which are oriented parallel to the diffusion direction . The Ca 2+ took ̃36h to completely penetrate the sols and transform it into calcium alginate gels.…”
Section: Methodsmentioning
confidence: 99%
“…This flow pattern is mapped during the cross‐linking of the polyelectrolyte chains by the cations and leads to a structure of parallel capillaries filled with aqueous solution . Ceramic membranes with an anisotropic pore structure can be formed from this self‐organization process by incorporating inorganic particles into the gel matrix, followed by subsequent ion exchange, drying, and sintering . The advantage of this method can be seen in its low cost and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Other strategies are exchange of the gelling ions or different drying procedures. Freeze, air and supercritical drying were studied when the interest on ceramic membranes aroused (Weber et al, 1997) and was further optimised Eljaouhari et al, 2006). Investigations by micro computer tomography (µCT) revealed that the pore structure was destroyed by ice crystals during freeze drying whereas the structure remained intact when water was exchanged against tert.…”
Section: Fig 5 Strategies Of Mineralisation -Which Also Can Be Usedmentioning
confidence: 99%
“…Only Weber et al (1997) described the synthesis of ceramic membranes based on structuring via sol-gel-process of ionotropic gelation of alginate/powder-slurries followed by calcination. Ceramic processing for membrane manufacturing was studied with Al 2 O 3 or TiO 2 including development of adapted drying regimes for the wet composites applying method inherent shrinkage, followed by heat treatment to obtain a sintered ceramic without cracks (Weber et al, 1997;Dittrich et al, 2002;Eljaouhari et al, 2006). Dittrich et al (2002) for the first time synthesised such ceramics consisting of the mineral phase of bone, hydroxyapatite, with parallel aligned pores and investigated their structure by µCT in cooperation with Goebbels et al (2002).…”
Section: Anisotropic Ceramicsmentioning
confidence: 99%